Polypropylene cable material as well as preparation method and application thereof
By modifying the compatibility modification of TiO2-ZnO composite nanoparticles and polymer matrix, combined with the formulation system of polypropylene cable materials, the problem of insufficient volume resistivity of polypropylene cable materials is solved, and the insulation performance and dielectricity are significantly improved performance.
Patent Information
- Application Number
- CN202411567834.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-14
AI Technical Summary
The volume resistivity of existing polypropylene cable materials is difficult to reach above 1015Ω·m, which affects its insulation performance.
Modified TiO2-ZnO composite nanoparticles are prepared by solvothermal reaction and modified with silane coupling agent to improve the compatibility and dispersion of nanoparticles, and combined with homopolypolypropylene, copolymerized polypropylene and ethylene-octene. to form cable material with high insulation performance.
The volume resistivity, dielectric properties and electric breakdown field strength of polypropylene cable material have been significantly improved, reaching 20℃ volume resistivity ≥1015Ω·m, 20℃ AC electrical strength ≥55kV/mm, and 20℃ relative dielectric constant ≤ 2.5.
Smart Images

Figure BDA0005119718030000051 
Figure BDA0005119718030000091 
Figure BDA0005119718030000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wire and cable materials, in particular to a polypropylene cable material and a preparation method and application thereof. Background Art
[0002] Polypropylene insulation material has become an emerging environmentally friendly and recyclable power cable insulation material. In addition, it has the advantages of excellent mechanical properties, stable chemical properties, low price, good heat resistance and electrical insulation performance. As a cable insulation material, the insulation performance of polypropylene is an important factor affecting its use. The volume resistivity of most polypropylene material matrices at 20°C can reach 10 15 Ω·m order of magnitude, but different degrees of modification will be carried out based on the use environment and conditions, such as mechanical toughening, grafting and blending are the main modification methods, but polypropylene grafting different groups or introducing other substances into the blending will cause the material polarity to change or the mixing to be uneven, thus affecting the insulation performance, which is manifested as a decrease in volume resistivity, down to 10 15 Below Ω·m, which greatly limits its use.
[0003] Invention patent CN113563666A discloses a high-temperature-resistant polypropylene cable insulation material and a preparation method thereof. The solution uses a grinding stirrer, a twin-screw extruder, and a pelletizer to melt-blend polypropylene, an antioxidant, a dispersant, and silicon nitride to prepare a polypropylene cable material. Inorganic fillers such as mica, aluminum hydroxide, magnesium hydroxide, and calcium carbonate added to the filler can increase the insulation performance of the polypropylene cable material, but the increase effect is limited, and the volume resistivity at 20°C is only 10 14 Invention patent CN117624774A discloses a polypropylene insulation material for power cables and a preparation method thereof. The solution uses a high-speed blender, a twin-screw extruder, and a pelletizer to melt-blend polypropylene, a modifier, a lubricant, an antioxidant, an anti-copper agent, etc. to prepare a polypropylene cable material, but the volume resistivity at 20°C is only 10 14 Invention patent CN117467217A discloses a method for preparing a modified polypropylene cable material and a modified polypropylene cable material. The method uses a torque rheometer to melt-blend polypropylene, hydrogenated styrene butadiene styrene block copolymer grafted with maleic anhydride, calcium stearate or magnesium stearate to prepare a modified polypropylene cable material. However, the volume resistivity at 20°C is only 10 14 The order of magnitude is Ω·m.
[0004] Therefore, it is a great challenge to improve the volume resistivity of polypropylene cable materials. Summary of the invention
[0005] Based on this, the purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a high-insulation polypropylene cable material and a preparation method and application thereof.
[0006] To achieve the above object, the technical scheme adopted by the present invention is: a polypropylene cable material, comprising the following components in parts by weight: 25-45 parts of homopolypropylene, 25-45 parts of copolymer polypropylene, 25-45 parts of ethylene-octene copolymer, 1-3 parts of modified TiO2-ZnO composite nanoparticles, and 0.1-8 parts of additives; a preparation method of the modified TiO2-ZnO composite nanoparticles, comprising the following steps:
[0007] (1) dissolving isopropyl titanate, zinc acetate and ammonia water in an organic solvent to carry out a solvothermal reaction to obtain TiO2-ZnO nanocomposite particles;
[0008] (2) dispersing the TiO2-ZnO nanocomposite particles in an organic solvent to obtain a mixture A, dissolving a silane coupling agent in an organic solvent to obtain a mixture B, mixing the mixture A and the mixture B for reaction, and refluxing, centrifuging, washing, and drying to obtain the modified TiO2-ZnO composite nanoparticles.
[0009] The invention provides a polypropylene cable material, wherein the formula system contains self-made modified TiO2-ZnO composite nanoparticles, wherein the nanoparticles are TiO2-ZnO nanocomposite particles modified by a silane coupling agent. The TiO2-ZnO nanoparticles can introduce many deep traps at the interface between a polymer matrix and the nanoparticles, and these deep traps cause the injected charge to be trapped near the electrode interface, and a large amount of space charge is bound near the interface between the medium and the electrode and cannot be injected into the medium, thereby improving the electric field distortion in the composite system, reducing the mobility of the charge, and further improving the overall volume resistivity, dielectric properties and electrical breakdown field strength of the material. However, pure TiO2-ZnO nanoparticles are inorganic particles and have poor compatibility with the polypropylene matrix, so the TiO2-ZnO nanoparticles need to be modified for compatibility. Through modification with silane coupling agent, the surface of TiO2-ZnO will have alkyl chains, which have high interfacial compatibility with the polypropylene matrix, and can greatly enhance the dispersibility of TiO2-ZnO nanoparticles in the matrix, thereby improving the compatibility between the matrix and nanoparticles in the composite material system, and thus improving the overall insulation performance of the material.
[0010] The polypropylene cable material prepared by the invention has high insulation performance, dielectric performance and breakdown field strength.
[0011] The present invention prepares modified TiO2-ZnO composite nanoparticles by a solvent thermal method, wherein isopropyl titanate is used as a titanium source, zinc acetate is used as a zinc source to provide titanium and zinc elements for the product, and ammonia water plays a role in adjusting the pH value. In the process of preparing the modified TiO2-ZnO composite nanoparticles of the present invention, the above raw materials are irreplaceable.
[0012] Preferably, in the step (1), the molar ratio of isopropyl titanate, zinc acetate and ammonia water is isopropyl titanate: zinc acetate: ammonia water = (1.8-2.2): (1.8-2.2): 1, and the mass ratio of the mixture of isopropyl titanate, zinc acetate, ammonia water and the organic solvent is 1: (5-10); the reaction temperature is 120-180°C, and the reaction time is 12-36h; preferably, the reaction time is 12-24h.
[0013] The inventors found in actual experiments that the ratio range of isopropyl titanate, zinc acetate and ammonia water will further affect the particle size of the prepared modified TiO2-ZnO composite nanoparticles, thereby further affecting the insulation properties, dielectric properties and breakdown field strength of the prepared polypropylene cable material.
[0014] The inventors found in actual experiments that the reaction time of isopropyl titanate, zinc acetate and ammonia water would affect the particle size of the prepared modified TiO2-ZnO composite nanoparticles, thereby further affecting the insulation properties, dielectric properties and breakdown field strength of the prepared polypropylene cable material.
[0015] Preferably, in step (1), the organic solvent includes at least one of methanol, ethanol and glycerol.
[0016] Preferably, in step (2), the mass ratio of the TiO2-ZnO nanocomposite particles to the organic solvent is 1:(5-10), the mass ratio of the silane coupling agent to the organic solvent is 1:(2-5), and the mass ratio of the mixture A to the mixture B is 1:(1-2);
[0017] Preferably, in step (2), the silane coupling agent is at least one of methyltrimethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and octadecyltrimethoxysilane.
[0018] More preferably, the silane coupling agent is octadecyltrimethoxysilane.
[0019] Preferably, in step (2), the reflux temperature is 110-120° C., and the reflux time is 10-12 h; the drying temperature is 60-65° C., and the drying time is 10-12 h.
[0020] Preferably, the particle size D50 of the modified TiO2-ZnO composite nanoparticles is 150-300 nm.
[0021] Preferably, the melt flow rate of the homopolypropylene is ≤3.5 g / 10 min, and the test condition is 230° C. / 2.16 kg; the melt flow rate of the copolymer polypropylene is ≤2.5 g / 10 min, and the test condition is 230° C. / 2.16 kg.
[0022] Preferably, the mass fraction of α-olefin in the ethylene-octene copolymer is 20%-35%.
[0023] Further preferably, the ethylene-octene copolymer is at least one of POE 8150, POE 6202, POE 3980, and POE 2070.
[0024] Preferably, the auxiliary agent is at least one of an ultraviolet light absorber, a light stabilizer, an antioxidant, and white oil.
[0025] Preferably, the weight portion of the ultraviolet light absorber is 0.1-1 part, and the ultraviolet light absorber is at least one of UV329, UV326, and C81.
[0026] Preferably, the weight portion of the light stabilizer is 0.1-1 part, and the light stabilizer is UV 770.
[0027] Preferably, the antioxidant is present in an amount of 0.1-1 parts by weight, and the antioxidant includes a primary antioxidant and an auxiliary antioxidant, wherein the primary antioxidant is one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol, 4,4'-thiobis(6-tert-butyl-3-methylphenol), triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate. The auxiliary antioxidant is one of tris(2,4-di-tert-butylphenyl) phosphite, dilauryl thiodipropionate, and bis(2,4-tert-butylphenyl) pentaerythritol diphosphite.
[0028] Preferably, the weight portion of the white oil is 0.1-2 parts, and the white oil is at least one of 3#, 5#, 7#, 10#, 15#, 26#, 32#, 48#, 68#, 90#, and 100#.
[0029] In addition, the present invention provides a method for preparing the polypropylene cable material, comprising the following steps:
[0030] S1: Put all the above raw materials into a mixer and mix them evenly;
[0031] S2: putting the uniformly mixed materials into a twin-screw extruder, extruding and pelletizing, and drying to obtain the polypropylene cable material.
[0032] Preferably, the heating intervals of the extruder in S2 are as follows: zone 1: 100-140°C, zone 2: 175-215°C, zone 3: 175-215°C, zone 4: 180-220°C, zone 5: 180-220°C, zone 6: 180-220°C, zone 7: 175-215°C, zone 8: 175-215°C, zone 9: 180-220°C, zone 10: 180-220°C, and the screw speed is 150-350r / min.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a polypropylene cable material, wherein the formula system contains self-made modified TiO2-ZnO composite nanoparticles, and the nanoparticles are TiO2-ZnO nanocomposite particles modified by silane coupling agents. TiO2-ZnO nanoparticles can introduce many deep traps at the interface between the polymer matrix and the nanoparticles, and these deep traps cause the injected charge to be trapped near the electrode interface, and a large amount of space charge is bound near the interface between the medium and the electrode and cannot be injected into the medium, thereby improving the electric field distortion in the composite system, reducing the mobility of the charge, and thus improving the overall volume resistivity, dielectric properties and electrical breakdown field strength of the material. However, pure TiO2-ZnO nanoparticles are inorganic particles and have poor compatibility with the polypropylene matrix, so the TiO2-ZnO nanoparticles need to be modified for compatibility. Through modification with silane coupling agent, the surface of TiO2-ZnO will have alkyl chains, which have high interfacial compatibility with the polypropylene matrix, and can greatly enhance the dispersibility of TiO2-ZnO nanoparticles in the matrix, thereby improving the compatibility between the matrix and nanoparticles in the composite material system, and thus improving the overall insulation performance of the material. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.
[0035] The main raw materials used in the examples and comparative examples of the present invention are described below, as shown in Table 1, but are not limited to these materials:
[0036] Table 1
[0037]
[0038]
[0039] Modified TiO2-ZnO composite nanoparticles-1
[0040] The preparation method of the modified TiO2-ZnO composite nanoparticle-1 comprises the following steps:
[0041] (1) dissolving isopropyl titanate, zinc acetate and ammonia water in an organic solvent for solvothermal reaction at a reaction temperature of 120° C. for a reaction time of 24 h to obtain TiO2-ZnO nanocomposite particles; the molar ratio of the isopropyl titanate, zinc acetate and ammonia water is isopropyl titanate: zinc acetate: ammonia water = 2:2:1; the mass ratio of the mixture of isopropyl titanate, zinc acetate and ammonia water to the organic solvent is 1:5;
[0042] (2) dispersing the TiO2-ZnO nanocomposite particles in an organic solvent to obtain a mixture A, dissolving a silane coupling agent in an organic solvent to obtain a mixture B, mixing the mixture A and the mixture B for reaction, and refluxing, centrifuging, washing, and drying to obtain the modified TiO2-ZnO composite nanoparticles.
[0043] The mass ratio of TiO2-ZnO nanocomposite particles to the organic solvent is 1:5; the mass ratio of the silane coupling agent to the organic solvent is 1:2; and the mass ratio of the mixture A to the mixture B is 1:1;
[0044] The silane coupling agent is octadecyltrimethoxysilane; the reflux temperature is 110° C., and the reflux time is 12 h; the drying temperature is 60° C., and the drying time is 12 h.
[0045] Modified TiO2-ZnO composite nanoparticles-2
[0046] The preparation method of the modified TiO2-ZnO composite nanoparticle-2 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the reaction temperature of step (1) is 180°C for the reaction of isopropyl titanate, zinc acetate and ammonia water to obtain TiO2-ZnO nanocomposite particles; the remaining components, amounts and preparation methods are exactly the same.
[0047] Modified TiO2-ZnO composite nanoparticles-3
[0048] The preparation method of the modified TiO2-ZnO composite nanoparticle-3 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the reaction time of step (1) is 12 hours for isopropyl titanate, zinc acetate and ammonia water to obtain TiO2-ZnO nanocomposite particles; the remaining components, amounts and preparation methods are exactly the same.
[0049] Modified TiO2-ZnO composite nanoparticles-4
[0050] The preparation method of the modified TiO2-ZnO composite nanoparticle-4 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the reaction time of step (1) is 36 hours for isopropyl titanate, zinc acetate and ammonia water to obtain TiO2-ZnO nanocomposite particles; the remaining components, amounts and preparation methods are exactly the same.
[0051] Modified TiO2-ZnO composite nanoparticles-5
[0052] The preparation method of the modified TiO2-ZnO composite nanoparticle-5 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the mass ratio of the mixture of isopropyl titanate, zinc acetate, and ammonia water to the organic solvent in step (1) is 1:10; the other components, amounts, and preparation methods are exactly the same.
[0053] Modified TiO2-ZnO composite nanoparticles-6
[0054] The preparation method of the modified TiO2-ZnO composite nanoparticle-6 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the molar ratio of isopropyl titanate, zinc acetate and ammonia water in step (1) is different, that is, the molar ratio of isopropyl titanate: zinc acetate: ammonia water = 1.8:2.2:1; the other components, amounts and preparation methods are exactly the same.
[0055] Modified TiO2-ZnO composite nanoparticles-7
[0056] The preparation method of the modified TiO2-ZnO composite nanoparticle-7 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the molar ratio of isopropyl titanate, zinc acetate and ammonia water in step (1) is different, that is, the molar ratio of isopropyl titanate: zinc acetate: ammonia water = 2.2:1.8:1; the other components, amounts and preparation methods are exactly the same.
[0057] Modified TiO2-ZnO composite nanoparticles-8
[0058] The preparation method of the modified TiO2-ZnO composite nanoparticle-8 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the silane coupling agent in step (2) is methyltrimethoxysilane; the other components, dosages and preparation methods are exactly the same.
[0059] Modified TiO2-ZnO composite nanoparticles-9
[0060] The preparation method of the modified TiO2-ZnO composite nanoparticle-9 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the mass ratio of the mixture A and the mixture B in step (2) is different, and the temperature and time of the reflux drying in step (2) are different;
[0061] The mass ratio of the mixture A to the mixture B is 1:2, the reflux temperature is 120° C., and the reflux time is 10 h; the drying temperature is 65° C., and the drying time is 10 h; the other components, dosages and preparation methods are exactly the same.
[0062] Modified TiO2-ZnO composite nanoparticles-10
[0063] The preparation method of the modified TiO2-ZnO composite nanoparticle-10 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the raw material selection in step (1) is different, and titanium chloride is used instead of isopropyl titanate as the titanium source; the other components, amounts and preparation methods are exactly the same.
[0064] Modified TiO2-ZnO composite nanoparticles-11
[0065] The preparation method of the modified TiO2-ZnO composite nanoparticle-11 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the raw material selection in step (1) is different, and zinc sulfate is used instead of zinc acetate as the zinc source; the other components, amounts and preparation methods are exactly the same.
[0066] Modified TiO2-ZnO composite nanoparticles-12
[0067] The preparation method of the modified TiO2-ZnO composite nanoparticle-12 is different from that of the modified TiO2-ZnO composite nanoparticle-1, except that the raw material selection in step (1) is different, and ammonia water is replaced by NaOH; the other components, dosages and preparation methods are exactly the same.
[0068] Examples and Comparative Examples
[0069] The present invention provides a polypropylene cable material. The components and weight portions of the polypropylene cable material are selected as shown in Table 2-Table 3. The preparation method of the polypropylene cable material comprises the following steps:
[0070] S1: Put all the above raw materials into a mixer and mix them evenly;
[0071] S2: putting the uniformly mixed materials into a twin-screw extruder, extruding and pelletizing, and drying to obtain the polypropylene cable material; the set temperatures of the twin-screw extruder are: zone 1: 140°C, zone 2: 175°C, zone 3: 215°C, zone 4: 220°C, zone 5: 220°C, zone 6: 220°C, zone 7: 215°C, zone 8: 215°C, zone 9: 220°C, zone 10: 220°C, and the screw speed is 350r / min.
[0072] Performance Testing
[0073] Test process: The cable materials prepared in the embodiment and the comparative example are respectively prepared into samples of the same size. The specific sample preparation process is: put them on a flat vulcanizer, preheat them at 200℃ for 10min, and then prepare the sample at 15MPa / 200℃ / 5min. Test according to the following standards:
[0074] GB / T 31838.2-2019 Dielectric and resistance properties of solid insulating materials;
[0075] GB / T 1408.1-2016 Test method for electrical strength of insulating materials;
[0076] GB / T 1409-2006 Recommended method for measuring the permittivity and dielectric loss factor of electrical insulating materials at power frequency, audio frequency, and high frequency (including meter-wave wavelength);
[0077] The polypropylene cable materials in the above embodiments and comparative examples were tested for volume resistivity at 20°C, AC electrical strength at 20°C (50 Hz), and relative dielectric constant at 20°C (50 Hz). The test results are shown in the following table.
[0078] Table 2
[0079]
[0080]
[0081]
[0082] Table 3
[0083]
[0084]
[0085] It can be seen from the above table that the volume resistivity of the polypropylene cable material provided by the present invention at 20°C is ≥10 15Ω·m, AC electrical strength at 20℃≥55kV / mm, relative dielectric constant at 20℃≤2.5.
[0086] From the comparison of Example 1, Examples 4-11, and Comparative Examples 1-3, it can be seen that the type of modified TiO2-ZnO composite nanoparticles will affect the insulation performance, dielectric properties and breakdown field strength of the polypropylene cable material finally prepared. The modified TiO2-ZnO composite nanoparticles prepared by the present invention using a specific preparation method have a particle size D50 of 150-300nm, good blending effect, and better insulation performance, dielectric properties and breakdown field strength.
[0087] Example 6 uses modified TiO2-ZnO composite nanoparticles-4, and the preparation process reaction time is long, and the particle size D50 is large, which affects the blending effect, resulting in slightly poor insulation performance, dielectric properties and breakdown field strength. Example 10 uses modified TiO2-ZnO composite nanoparticles-8, and the selection of silane coupling agents in the preparation process is different, resulting in slightly poor insulation performance, dielectric properties and breakdown field strength.
[0088] Comparative Example 1 uses modified TiO2-ZnO composite nanoparticles-10, and titanium chloride is used to replace isopropyl titanate as the titanium source in the preparation process; Comparative Example 2 uses modified TiO2-ZnO composite nanoparticles-11, and zinc sulfate is used to replace zinc acetate as the zinc source in the preparation process; Comparative Example 3 uses modified TiO2-ZnO composite nanoparticles-12, and NaOH is used to replace ammonia water in the preparation process; the raw materials in Comparative Examples 1-3 cannot further participate in the reaction, cannot be dissolved in ethanol, cannot play a role in adjusting the pH value, and will also introduce other metal elements to pollute the product, thereby further leading to poor insulation performance, dielectric properties and breakdown field strength of polypropylene cable materials.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polypropylene cable material, characterized in that: The invention comprises the following components in parts by weight: 25-45 parts of homopolypropylene, 25-45 parts of copolymer polypropylene, 25-45 parts of ethylene-octene copolymer, 1-3 parts of modified TiO2-ZnO composite nanoparticles, and 0.1-8 parts of auxiliary agent; the preparation method of the modified TiO2-ZnO composite nanoparticles comprises the following steps: (1) dissolving isopropyl titanate, zinc acetate and ammonia water in an organic solvent to carry out a solvothermal reaction to obtain TiO2-ZnO nanocomposite particles; (2) dispersing the TiO2-ZnO nanocomposite particles in an organic solvent to obtain a mixture A, dissolving a silane coupling agent in an organic solvent to obtain a mixture B, mixing the mixture A and the mixture B for reaction, and refluxing, centrifuging, washing, and drying to obtain the modified TiO2-ZnO composite nanoparticles.
2. The polypropylene cable material according to claim 1, characterized in that: In the step (1), the molar ratio of isopropyl titanate, zinc acetate and ammonia water is isopropyl titanate: zinc acetate: ammonia water = (1.8-2.2): (1.8-2.2): 1, and the mass ratio of the mixture of isopropyl titanate, zinc acetate, ammonia water and organic solvent is 1: (5-10); the reaction temperature is 120-180°C, and the reaction time is 12-36h; preferably, the reaction time is 12-24h.
3. The polypropylene cable material according to claim 1, characterized in that: In the step (2), the mass ratio of the TiO2-ZnO nanocomposite particles to the organic solvent is 1:(5-10), the mass ratio of the silane coupling agent to the organic solvent is 1:(2-5), and the mass ratio of the mixture A to the mixture B is 1:(1-2).
4. The polypropylene cable material according to claim 1, characterized in that: In the step (2), the silane coupling agent is at least one of methyltrimethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and octadecyltrimethoxysilane.
5. The polypropylene cable material according to claim 1, characterized in that: In the step (2), the reflux temperature is 110-120° C., and the reflux time is 10-12 h; the drying temperature is 60-65° C., and the drying time is 10-12 h.
6. The polypropylene cable material according to claim 1, characterized in that: The particle size D50 of the modified TiO2-ZnO composite nanoparticles is 150-300nm.
7. The polypropylene cable material according to claim 1, characterized in that: The melt flow rate of the homopolypropylene is ≤3.5 g / 10 min, and the test condition is 230° C. / 2.16 kg; the melt flow rate of the copolymer polypropylene is ≤2.5 g / 10 min, and the test condition is 230° C. / 2.16 kg.
8. The polypropylene cable material according to claim 1, characterized in that: The mass fraction of α-olefin in the ethylene-octene copolymer is 20%-35%.
9. The polypropylene cable material according to claim 1, characterized in that: The auxiliary agent is at least one of an ultraviolet light absorber, a light stabilizer, an antioxidant, and white oil.
10. A method for preparing a polypropylene cable material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Put all the above raw materials into a mixer and mix them evenly; S2: putting the uniformly mixed materials into a twin-screw extruder, extruding and pelletizing, and drying to obtain the polypropylene cable material.
Citation Information
Patent Citations
High-temperature-resistant-grade polypropylene cable insulation material and preparation method thereof
CN113563666A
Preparation method of modified polypropylene cable material and modified polypropylene cable material
CN117467217A
Polypropylene insulation material for power cable and preparation method of polypropylene insulation material
CN117624774A